2016
DOI: 10.3390/v8100293
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin in Influenza Virus Entry and Innate Immunity

Abstract: Viruses are obligatory cellular parasites. Their mission is to enter a host cell, to transfer the viral genome, and to replicate progeny whilst diverting cellular immunity. The role of ubiquitin is to regulate fundamental cellular processes such as endocytosis, protein degradation, and immune signaling. Many viruses including influenza A virus (IAV) usurp ubiquitination and ubiquitin-like modifications to establish infection. In this focused review, we discuss how ubiquitin and unanchored ubiquitin regulate IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 123 publications
0
47
0
1
Order By: Relevance
“…For influenza, several different interactions with the ubiquitin system have been identified that critically influence the outcome of the infection [126]. Generally, the activation of the RIG-I -MAVS -irf3 signaling axis in type I IFN signaling, which is important for all viruses discussed in this review, is governed by ubiquitin linked through its lysine at position 63 (forming K63-linked chains).…”
Section: Manipulation Of Ubiquitin and Isg15 Regulated Innate Immunementioning
confidence: 99%
“…For influenza, several different interactions with the ubiquitin system have been identified that critically influence the outcome of the infection [126]. Generally, the activation of the RIG-I -MAVS -irf3 signaling axis in type I IFN signaling, which is important for all viruses discussed in this review, is governed by ubiquitin linked through its lysine at position 63 (forming K63-linked chains).…”
Section: Manipulation Of Ubiquitin and Isg15 Regulated Innate Immunementioning
confidence: 99%
“…The data underline that CD81 interacting proteins function in HCV entry. The discovery of CBL and CBLB as HCV host factors are in line with findings showing that ubiquitination Table. https://doi.org/10.1371/journal.ppat.1007111.g002 events are required in endocytosis and entry of viruses of diverse families including influenza virus and adenoviruses [30,31].…”
Section: A Subset Of Cd81 Interacting Proteins Is Required For Full Hmentioning
confidence: 99%
“…The UPS is a doubleedged sword in viral pathogenesis; host cells employ the UPS to degrade viral proteins to limit viral infection, but viruses can manipulate the UPS machinery to degrade cellular restriction factors, thereby facilitating viral propagation. To date, many viruses have been reported to reprogram the UPS to satisfy their needs, and the UPS can function in different stages of the viral life cycle, including viral capsid uncoating [35,36], viral replication [37][38][39], gene transcription [40,41], viral envelopment [42], and viral progeny release [43,44]. Furthermore, the UPS was reported to play an important role during various stages of the coronavirus (CoV) infection cycle [45], and it could potentially be developed as a drug target to modulate the impact of CoV infection in the future.…”
Section: Viruses Manipulate the Ups To Favour Viral Propagationmentioning
confidence: 99%